2012
DOI: 10.1111/j.1758-2229.2012.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

The origin of cyanobacteria in Antarctic sea ice: marine or freshwater?

Abstract: Cyanobacteria play an important role in the primary productivity of many ecosystems and are dominant in non-marine polar environments. Apart from detecting low levels of cyanobacteria-like pigments in the Southern Ocean, little effort has been spent in trying to elucidate Cyanobacteria in Antarctic sea ice. Here, we report the first use of culture, microscope, microarray and molecular techniques to show that marine Cyanobacteria are rare or absent in sea ice. Our infrequent positive signals were most closely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…Putative nitrogen-fixing cyanobacteria were only amplified in one sample in the Central Arctic Ocean (upper part of the ice at -0.2°C), supporting previous hypotheses that this group of nitrogen-fixers has not realized a niche in ice-covered polar open oceans (Murphy and Haugen, 1985; Koh et al, 2012b). However, other nitrogen-fixing cyanobacteria have been detected in snow (Harding et al, 2011; Boetius et al, 2015), glacial environments (Yallop et al, 2012; Vonnahme et al, 2015), hydrothermal vents (Mehta et al, 2003), and in other cold environments, such as Antarctic lakes (Olson et al, 1998) and sea ice (Koh et al, 2012a). Therefore, it remains unclear why they have not populated nitrogen-limited marine Arctic waters.…”
Section: Discussionmentioning
confidence: 99%
“…Putative nitrogen-fixing cyanobacteria were only amplified in one sample in the Central Arctic Ocean (upper part of the ice at -0.2°C), supporting previous hypotheses that this group of nitrogen-fixers has not realized a niche in ice-covered polar open oceans (Murphy and Haugen, 1985; Koh et al, 2012b). However, other nitrogen-fixing cyanobacteria have been detected in snow (Harding et al, 2011; Boetius et al, 2015), glacial environments (Yallop et al, 2012; Vonnahme et al, 2015), hydrothermal vents (Mehta et al, 2003), and in other cold environments, such as Antarctic lakes (Olson et al, 1998) and sea ice (Koh et al, 2012a). Therefore, it remains unclear why they have not populated nitrogen-limited marine Arctic waters.…”
Section: Discussionmentioning
confidence: 99%
“…Pigment-based confirmation is questionable however as phycoerythrin and phycocyanin are also present in other algae including Cryptophytes which are common during Antarctic coastal blooms [54]. To potentially validate these earlier findings, a multi-method molecular analysis was recently carried out on fast-ice cores extracted from sites spanning 300 km in the Ross Sea region of Antarctica [55]. Clone libraries were constructed from the 16S rDNA gene, the internal transcribed sequence (ITS) region and the cyanobacterial core RNA polymerase ( rpo C).…”
Section: Bacteria With Light-harvesting Capabilitiesmentioning
confidence: 99%
“…Data from the ITS and microarray analysis of these sea ice samples showed close affiliation to the freshwater cyanobacteria Phormidium sp. and Cylindrospermopsis sp., respectively [55], but the closest Antarctic relative was an uncultured cyanobacteria clone from the nearby meromictic Lake Fryxell [42]. Aerobiology studies conducted in the Antarctic [57,58] and the Arctic [59] suggested that much of the biological material present in the air originates locally.…”
Section: Bacteria With Light-harvesting Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regarding their very low abundance in the polar oceans, picocyanobacteria probably play little role on the pelagic carbon and energy flow in this part of the globe (Díez et al, 2012;Gradinger and Lenz, 1989;Koh et al, 2012).…”
Section: Diversity In the Arctic Oceanmentioning
confidence: 99%